A Fibrinolytic Agent from a Saturnid Caterpillar Partial Purification and Characterization - Arocha-Pinango, C. L; Marsh, N. A; Robinson, D (Thrombosis and Haemostasis, 1973)
Purification and characterization studies were performed on a proteolytic agent obtained from a Saturnid moth caterpillar. Starting material possessed caseinolytic, fibrinolytic and plasminogen-activator activities. The fibrinolytic activity was stable over a wide range of pH and temperature. Purification was performed by molecular exclusion chromatography and ion exchange chromatography. A pH- and heat-stable material was obtained having a molecular weight in the range of 16,000-18,000. This material did not possess the ability to activate human plasminogen but retained direct caseinolytic and fibrinolytic activities. It had no effect on thrombin- and arvin- clotting times of human plasma, on partial thromboplastin time or on the whole blood thrombin generation test. Electrophoresis on cellulose acetate agar gel and polyacrylamide showed the material to be very basic and moving away from any detectable protein. The isoelectric point was found to be greater than pH 10. The relationship between the characterized material and the clinical syndrome caused by contact with the caterpillar remains to be determined.